El final del rey Ptolomeo de las Mauretaniae - Enrique Gozalbes Cravioto (Gerión, 2005)
The assassination of the king Ptolemaeo of Mauritania, accomplished to instances of the emperor Caius, it has motivated a vast discussion between the historians. In the present work are studied the different documental sources, are analyzed the interpretations that they have been formulated, collected a current state of topic referred to this political crime